A hole modulator for InGaN/GaN light-emitting diodes - Zhang, Zi-Hui (2015)
The low p-type doping efficiency of the p-GaN layer has severely limited the performance of InGaN/GaN light-emitting diodes (LEDs) due to the ineffective hole injection into the InGaN/GaN multiple quantum well (MQW) active region. The essence of improving the hole injection efficiency is to increase the hole concentration in the p-GaN layer. Therefore, in this work, we have proposed a hole modulator and studied it both theoretically and experimentally. In the hole modulator, the holes in a remote p-type doped layer are depleted by the built-in electric field and stored in the p-GaN layer. By this means, the overall hole concentration in the p-GaN layer can be enhanced. Furthermore, the hole modulator is adopted in the InGaN/GaN LEDs, which reduces the effective valance band barrier height for the p-type electron blocking layer from ∼332 meV to ∼294 meV at 80 A/cm2 and demonstrates an improved optical performance, thanks to the increased hole concentration in the p-GaN layer and thus the improved hole injection into the MQWs.